The Impact of Early Marriage Practice to the Increasement of Stunting Case in Jepara Regency - Imron Choeri; Munasir; Syamsul Ma'arif; Mashudi; Alfa Syahriar (CV. Creative Tugu Pena, 2026)
This study aims to explain the impact of early marriage on the increasing number of stunting cases in Jepara Regency. This research uses a qualitative approach with a case study method. Data collection techniques in this study include interviews, observations, and documentation. The data obtained were then analyzed using Miles and Huberman’s data analysis techniques, which consist of data reduction, data display, and conclusion drawing. The results of this study indicate that the practice of early marriage in Jepara remains high. Early marriage is caused by premarital pregnancy, traditions, low economic status, and low levels of education. Stunting cases in Jepara are also relatively high despite showing a decline. In 2024, stunting cases in Jepara reached 2,731. The factors contributing to stunting in Jepara include inadequate nutrition for pregnant women and toddlers, limited parental knowledge regarding nutrition and parenting, poor sanitation, low economic conditions, and early marriage. Based on the data analysis, it can be concluded that the case of early marriage and stunting in Jepara are quite high. Based on the analysis, it found that early marriage has significant influence toward the growth of stunting in Jepara. This study is expected to give contribution in preventing early marriage and stunting.